Giant piezoresistivity in a van der Waals material induced by intralayer atomic motions - Lingyun Tang; Zhongquan Mao; Chutian Wang; Qi Fu; Chen Wang; Yichi Zhang; Jingyi Shen; Yuefeng Yin; Bin Shen; Dayong Tan; Qian Li; Yonggang Wang; et al. (Nature Communications, 2023)
Lattice shrinkage is a dominating factor for the strain-induced change of the electronic properties in vdW layered materials. Here, the authors discover a piezoresistivity in pressurized β′-In2Se3, which originates from the intralayer atomic motions.